Does testing enhance learning in continuing medical education? - McConnell, Meghan; Hou, Chenchen; Panju, Mohamed; Panju, Akbar; Azzam, Khalid (Canadian Medical Education Journal, 2018)
Background: There has been growing interest in using theory-driven research to develop and evaluate continuing medical education (CME) activities. Within health professions education, testing has been shown to promote learning in a variety of different contexts, an effect referred to as test-enhanced learning (TEL). However, the extent to which TEL generalizes to CME remains unclear. The purpose of this study was to investigate whether physicians who received two intervening tests following a CME event would experience a TEL effect relative to physicians who received additional study material to review without testing. Methods: Forty-nine physicians were recruited during a local CME activity. Physicians were randomized to either a) the test group (n=26), where participants completed two 20 multiple-choice question (MCQ) quizzes related to the lecture content or b) the study group (n=23), where participants studied the same information without testing. Testing and studying occurred independently during the CME activity, and then four weeks later online. At eight weeks, participants completed a final 20-item MCQ online test. A between-subjects t-test was used to compare performance on the final test as a function of the initial educational activity (test group vs. study group). Results: Performance on the final MCQ test was equivalent for both test (Mean (SD): 75% (9.9)) and study-only (77% (7.3)) conditions (t(47) = 0.94, p=0.35). Conclusion: The null findings in the present study are contrary to previous findings demonstrating TEL among novice learner populations. The lack of TEL highlights several programmatic considerations that should be factored in before implementing TEL as a part of CME.